Alumina-based composite oxide and method for producing alumina-based composite oxide

By accurately controlling the distribution of elements of alumina, cerium and zirconia in the third-level particles, the problem of catalyst metal elements agglomeration in the high-temperature zone is solved, and the stability and activity of the catalyst are improved.

CN119866314APending Publication Date: 2025-04-22DAIICHI KIGENSO KAGAKU KOGYO CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480003985.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-31
Filing Date
2024-03-22
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

When exposed to the high temperature zone for a long time, the catalyst metal elements tend to condense on the composite oxide containing alumina, resulting in the catalyst deactivation.

Method used

By controlling the elemental distribution of composite oxides containing alumina with high precision, we ensure that the alumina, cerium oxide and zirconia are evenly distributed in the third-level particles, thereby inhibiting the aggregation of metal catalyst elements.

Benefits of technology

The aggregation of the catalyst metal elements in the high temperature zone is effectively inhibited, the activity of the catalyst is maintained, and the activity of the catalyst is further improved through the action of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119866314A_ABST
    Figure CN119866314A_ABST
Patent Text Reader

Abstract

An alumina-based composite oxide containing: alumina; and cerium oxide and / or zirconium oxide, and satisfies all of the following requirements (1) to (4) in point analysis at a total of 50 points by energy dispersive X-ray spectroscopy: (1) at 50 points, there is at least one measurement point at which the alumina content is 50-99 mass% and the content of an element oxide other than alumina is 1-50 mass%; (2) at 50 points, there is 1 or more measurement points at which the alumina content is 1% by mass or more and less than 50% by mass, and the content of element oxides other than alumina is 50% by mass or less and 99% by mass or less; (3) the difference between the maximum value and the minimum value of the alumina content at 50 measurement points is 20-95 (inclusive); and (4) the difference between the maximum value and the minimum value of the content of the element oxides other than alumina at 50 measurement points is 20-95 (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an alumina-based composite oxide and a method for producing the alumina-based composite oxide. Background Art

[0002] When driving in high-speed and ultra-high-speed areas, the exhaust gas temperature will increase significantly, which has also been included in the exhaust emission standard model in recent years. Therefore, compared with the past, the operating temperature of the exhaust gas purification catalyst will also be significantly higher, making it difficult to suppress the aggregation caused by the sintering of the catalyst metal elements.

[0003] Patent document 1 discloses a composite metal oxide porous body, which is a mixture of first ultrafine particles containing aluminum oxide and second ultrafine particles containing zirconium oxide as a composite metal oxide porous body that can be used as a catalyst carrier, wherein for all metal elements containing more than 0.1 mass % in the porous body, the first ultrafine particles and the second ultrafine particles are uniformly dispersed to meet the following conditions: by using energy dispersive X-ray spectrometry using a scanning transmission electron microscope with a spherical aberration correction function, the standard deviation of the content of each metal element obtained by measuring the content (mass %) of the metal element within a small analysis range of 20 nm square at 100 measuring points is less than 10 (refer to claim 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent document 1: International Publication No. 2011 / 030875. Summary of the invention

[0007] Problem that the invention aims to solve

[0008] Conventionally, in alumina-containing composite oxides for supporting catalyst metal elements, materials having uniform element distribution have been used as shown in Patent Document 1 in order to suppress aggregation of catalyst metal elements when exposed to a high temperature region for a long period of time.

[0009] However, the inventors have found that when the element distribution of the composite oxide containing aluminum oxide is extremely uniform, if it is exposed to a high temperature zone for a long time, the metal catalyst element may condense on the element that is easily deactivated in the composite oxide containing aluminum oxide.

[0010] The present invention has been made in view of the above problems, and its purpose is to provide an aluminum oxide-containing composite oxide that can further suppress the aggregation of catalyst metal elements when exposed to high temperature for a long time. It also provides a method for producing an aluminum oxide-based composite oxide that can obtain the aluminum oxide-based composite oxide.

[0011] Solutions for solving problems

[0012] To solve the above problems, the inventors conducted in-depth research on composite oxides containing aluminum oxide and found that by appropriately controlling the element distribution of composite oxides containing aluminum oxide with high precision, the aggregation of catalyst metal elements when exposed to high temperature for a long time can be further suppressed, thereby completing the present invention.

[0013] That is, the present invention provides the following:

[0014] [1] An alumina-based composite oxide, characterized by comprising:

[0015] Alumina; and

[0016] Cerium oxide and / or zirconium oxide,

[0017] In the point analysis of a total of 50 points performed according to the following steps a to c using energy dispersive X-ray spectroscopy, all of the following requirements (1) to (4) are satisfied:

[0018] (1) Among the 50 points, at least one measurement point exists where the aluminum oxide content is 50 mass % to 99 mass % and the content of the oxide of the element other than aluminum oxide is 1 mass % to 50 mass %;

[0019] (2) Among the 50 points, at least one measurement point exists where the aluminum oxide content is 1 mass % or more and less than 50 mass % and the content of the oxide of the element other than aluminum oxide is 50 mass % or less and less than 99 mass %;

[0020] (3) The difference between the maximum and minimum values ​​of the aluminum oxide content at the 50 measurement points is 20 or more and 95 or less;

[0021] (4) The difference between the maximum and minimum values ​​of the content of oxides of elements other than aluminum oxide at 50 measurement points is 20 or more and 95 or less,

[0022] <Steps>

[0023] a: From the particle images observed by scanning electron microscopy, select a particle image with a cross section of more than 4 μm in the longitudinal direction and more than 4 μm in the lateral direction;

[0024] b: Composition analysis was performed at 25 measurement points at intervals of 1 μm within a range of 4 μm in the longitudinal direction and 4 μm in the lateral direction of the selected particle image;

[0025] c: Select another particle image different from the particle image selected in step a, and perform the same composition analysis as in step b.

[0026] According to the above-mentioned structure, in particles having a cross section of more than 4 μm in the longitudinal direction and more than 4 μm in the lateral direction, there are differences in element distribution that satisfy the above (1) to (4). That is, in the tertiary particles constituting the alumina-based composite oxide, there are some differences in element distribution. Therefore, when the metal catalyst element is loaded on the alumina-based composite oxide, the metal catalyst element will be preferentially loaded on the element with high affinity. When the affinity with the carrier is high, even if it is exposed to a high temperature zone for a long time, due to the anchoring effect, etc., the aggregation between the metal catalyst elements can be suppressed, and the metal catalyst can also maintain a more active state. In addition, elements with a high affinity for the metal catalyst element are often used as co-catalysts. Therefore, the metal catalyst element is preferentially loaded next to the co-catalyst, which is expected to improve the catalyst activity. In addition, since alumina and the added metal element exist in the same tertiary particle, when exposed to a high temperature zone for a long time, alumina and the added metal element can act as a diffusion barrier to each other and suppress the degradation of the catalyst.

[0027] Furthermore, the present invention also provides the following contents:

[0028] [2] The alumina-based composite oxide according to [1], further satisfying all of the following requirements (5) to (6) in the 50-point analysis:

[0029] (5) Among the 50 points, at least one measurement point exists where the aluminum oxide content is 55 mass % to 99 mass % and the content of the oxide of the element other than aluminum oxide is 1 mass % to 45 mass %;

[0030] (6) Among the 50 points, there is at least one measurement point where the aluminum oxide content is 1 mass % to 45 mass % and the content of the element oxide other than aluminum oxide is 55 mass % to 99 mass %.

[0031] If the tertiary particles constituting the alumina-based composite oxide further satisfy the above-mentioned (5) to (6) in addition to the above-mentioned (1) to (4), aggregation of the metal catalyst element can be further suppressed.

[0032] Furthermore, the present invention also provides the following contents:

[0033] [3] The alumina-based composite oxide according to [1], further satisfying all of the following requirements (7) to (8) in the 50-point analysis:

[0034] (7) Among the 50 points, there are 10 or more measurement points where the aluminum oxide content is 50 mass % or more and 99 mass % or less and the content of the oxide of the element other than aluminum oxide is 1 mass % or more and 50 mass % or less;

[0035] (8) Among the 50 points, there are 10 or more measurement points where the aluminum oxide content is 1 mass % or more and less than 50 mass % and the content of the oxide of the element other than aluminum oxide is more than 50 mass % and less than 99 mass %.

[0036] According to the invention of [3] above, aggregation of metal catalyst elements can be further suppressed.

[0037] Furthermore, the present invention also provides the following contents:

[0038] [4] The alumina-based composite oxide according to [2], further satisfying all of the following requirements (9) to (10) in the 50-point analysis:

[0039] (9) Among the 50 points, there are 5 or more measurement points where the aluminum oxide content is 55 mass % or more and 99 mass % or less and the content of the oxide of the element other than aluminum oxide is 1 mass % or more and 45 mass % or less;

[0040] (10) Among the 50 points, there are 5 or more measurement points where the aluminum oxide content is 1 mass % to 45 mass % and the content of the element oxide other than aluminum oxide is 55 mass % to 99 mass %.

[0041] In the tertiary particles constituting the alumina-based composite oxide, if there are differences that further satisfy the above (9) to (10) in addition to the above (1) to (4), aggregation of the metal catalyst element can be further suppressed.

[0042] Furthermore, the present invention also provides the following contents:

[0043] [5] The alumina-based composite oxide according to any one of [1] to [4], wherein the content of alumina in a composition analysis by an X-ray fluorescence method is 15 mass % or more and 80 mass % or less.

[0044] When the content of alumina is 15 mass % or more and 80 mass % or less in a composition analysis by an X-ray fluorescence method, the metal catalyst element is supported on the alumina-based composite oxide, and aggregation of the metal catalyst element can be further suppressed.

[0045] It should be noted that in the composition analysis obtained by X-ray fluorescence, the content of each oxide contained in the entire aluminum oxide-based composite oxide is obtained. On the other hand, in the point analysis using energy dispersive X-ray spectroscopy (the above [1], the above [2]), the content of each oxide at the surface measurement point as the analysis object is obtained, rather than the content of the entire aluminum oxide-based composite oxide.

[0046] Furthermore, the present invention also provides the following contents:

[0047] [6] The alumina-based composite oxide according to any one of [1] to [5], wherein the content of cerium oxide and / or zirconium oxide is 0.1 mass % to 85 mass % in a composition analysis by X-ray fluorescence.

[0048] Since cerium oxide and / or zirconium oxide are used as promoters, when the content of cerium oxide and / or zirconium oxide is 0.1 mass % or more, they are suitable for use as catalyst carriers. In addition, when the content of cerium oxide and / or zirconium oxide is 85 mass % or less, thermal degradation can be suppressed.

[0049] Furthermore, the present invention also provides the following contents:

[0050] [7] The alumina-based composite oxide according to any one of [1] to [6], comprising, as oxides other than alumina, cerium oxide, and zirconium oxide, at least one oxide of a rare earth element other than cerium and promethium.

[0051] When at least one oxide of a rare earth element other than cerium and promethium is included, the crystal phases of aluminum oxide, ceria, and zirconium oxide are stabilized, and degradation of the catalyst can be further suppressed.

[0052] Furthermore, the present invention also provides the following contents:

[0053] [8] A method for producing the alumina-based composite oxide according to any one of [1] to [7], comprising:

[0054] Step 1, adding acid to sodium aluminate to obtain hydrated alumina suspension A;

[0055] Step 2, preparing an aqueous solution B-1 containing an industrial salt of cerium and / or zirconium, and / or a suspension B-2 containing an industrial salt of cerium and / or zirconium;

[0056] Step 3, obtaining a precipitate of an aluminum composite precursor by mixing the suspension A with the aqueous solution B-1 and / or the suspension B-2; and

[0057] In step 4, the precipitate is heat-treated to obtain an alumina-based composite oxide.

[0058] The conventional coprecipitation method is effective for preparing composite oxides with uniform element distribution, but it is difficult to control the element distribution except for the solubility product difference of the precipitate. On the other hand, in the mixing method of mixing crystalline alumina with crystalline cerium oxide and zirconium oxide, the element distribution is such that the constituent elements of each tertiary particle are the same as before mixing, and the characteristics of the composite of alumina with cerium oxide and zirconium oxide are difficult to show.

[0059] In view of the above problems, according to the invention of [8], by mixing the hydrated alumina suspension A with the aqueous solution B-1 and / or suspension B-2 containing industrial salts of cerium and / or zirconium, the precursors of cerium oxide and zirconium oxide can be provided on the surface and / or inside the hydrated alumina. Thus, the secondary alumina particles containing cerium oxide and zirconium oxide and the secondary alumina particles containing cerium oxide and zirconium oxide can coexist in the tertiary particles of the alumina-based composite oxide. Furthermore, by controlling the aggregation of the hydrated alumina and the precursors of cerium oxide and zirconium oxide, the element distribution in the tertiary particles of the composite oxide can be controlled.

[0060] According to such a production method, an alumina-based composite oxide having the characteristics (1) to (4) in the above-mentioned [1] can be obtained.

[0061] Effects of the Invention

[0062] According to the present invention, an aluminum oxide-containing composite oxide can be provided that can further suppress the aggregation of catalyst metal elements when exposed to a high temperature region for a long time, and a method for producing an aluminum oxide-based composite oxide can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 This is a model diagram of the tertiary particles of the alumina-based composite oxide of Examples 1 to 34.

[0064] Figure 2 It is a model diagram of the tertiary particles of the alumina-based composite oxides of Comparative Examples 1, 3 to 5, 7, 9, 12 and 13.

[0065] Figure 3 It is a model diagram of the tertiary particles of the alumina-based composite oxides of Comparative Example 2, Comparative Example 6, Comparative Example 8, Comparative Example 10, and Comparative Example 14.

[0066] Figure 4 This is a model diagram of the tertiary particles of the alumina-based composite oxide of Comparative Example 11.

[0067] Figure 5 This is the X-ray diffraction spectrum of the alumina-based composite oxide of Example 1. DETAILED DESCRIPTION

[0068] The embodiments of the present invention are described below. However, the present invention is not limited to these embodiments. It should be noted that in this specification, the aluminum oxide composite oxide is a common aluminum oxide composite oxide containing 10% by mass or less of an impurity metal compound containing hafnium. In addition, in this specification, expressions such as "containing" and "including" include the concepts of "containing", "comprising", "substantially consisting of" and "consisting only of".

[0069] The maximum value and the minimum value of the content of each component shown below are independent of the content of other components and are respectively the preferred minimum value and the preferred maximum value in the present invention.

[0070] In addition, the maximum values ​​and minimum values ​​of various parameters (measured values, etc.) shown below are independent of the content (composition) of each component and are respectively the preferred minimum value and maximum value of the present invention.

[0071] [Alumina-based composite oxides]

[0072] The alumina-based composite oxide of the present embodiment is characterized by containing:

[0073] Alumina; and

[0074] Cerium oxide and / or zirconium oxide,

[0075] In the point analysis of a total of 50 points performed according to the following steps a to c using energy dispersive X-ray spectroscopy, all of the following requirements (1) to (4) are satisfied:

[0076] (1) Among the 50 points, at least one measurement point exists where the aluminum oxide content is 50 mass % to 99 mass % and the content of the oxide of the element other than aluminum oxide is 1 mass % to 50 mass %;

[0077] (2) Among the 50 points, at least one measurement point exists where the aluminum oxide content is 1 mass % or more and less than 50 mass % and the content of the oxide of the element other than aluminum oxide is 50 mass % or less and less than 99 mass %;

[0078] (3) The difference between the maximum and minimum values ​​of the aluminum oxide content at the 50 measurement points is 20 or more and 95 or less;

[0079] (4) The difference between the maximum and minimum values ​​of the content of oxides of elements other than aluminum oxide at 50 measurement points is 20 or more and 95 or less,

[0080] <Steps>

[0081] a: From the particle images observed by scanning electron microscopy, select a particle image with a cross section of more than 4 μm in the longitudinal direction and more than 4 μm in the lateral direction;

[0082] b: Composition analysis was performed at 25 measurement points at intervals of 1 μm within a range of 4 μm in the longitudinal direction and 4 μm in the lateral direction of the selected particle image;

[0083] c: Select another particle image different from the particle image selected in step a, and perform the same composition analysis as in step b.

[0084] According to the alumina-based composite oxide, in particles having a cross section of more than 4 μm in the longitudinal direction and more than 4 μm in the lateral direction, there are differences in element distribution that satisfy the above (1) to (4). That is, in the tertiary particles constituting the alumina-based composite oxide, there are some differences in element distribution. Therefore, when the metal catalyst element is loaded on the alumina-based composite oxide, the metal catalyst element will be preferentially loaded on the element with high affinity. When the affinity with the carrier is high, even if it is exposed to a high temperature zone for a long time, due to the anchoring effect, etc., the aggregation between the metal catalyst elements can be suppressed, and the metal catalyst can also maintain a more active state. In addition, elements with a high affinity for the metal catalyst element are often used as co-catalysts. Therefore, the metal catalyst element is preferentially loaded next to the co-catalyst, which is expected to improve the catalyst activity. In addition, since alumina and the added metal element exist in the same tertiary particle, when exposed to a high temperature zone for a long time, they can respectively act as diffusion barriers and suppress the degradation of the catalyst.

[0085] In this specification, tertiary particles refer to particles formed by agglomeration of secondary particles, and secondary particles refer to particles formed by agglomeration of crystal grains (primary particles).

[0086] From the viewpoint of suppressing the aggregation of the metal catalyst element, the number of measurement points satisfying the above-mentioned (1) is preferably 2 or more, more preferably 4 or more, further preferably 7 or more, and particularly preferably 10 or more.

[0087] From the viewpoint of suppressing the aggregation of the metal catalyst element, the number of measurement points satisfying the above-mentioned (1) is preferably 48 or less, more preferably 46 or less, further preferably 43 or less, and particularly preferably 40 or less.

[0088] From the viewpoint of suppressing the aggregation of the metal catalyst element, the measurement points satisfying the above (1) are preferably 2 to 48, more preferably 4 to 46, further preferably 7 to 43, and particularly preferably 10 to 40.

[0089] From the viewpoint of suppressing the aggregation of the metal catalyst element, the number of measurement points satisfying (2) is preferably 2 or more, more preferably 4 or more, further preferably 7 or more, and particularly preferably 10 or more.

[0090] From the viewpoint of suppressing the aggregation of the metal catalyst element, the number of measurement points satisfying the above-mentioned (2) is preferably 48 or less, more preferably 46 or less, further preferably 43 or less, and particularly preferably 40 or less.

[0091] From the viewpoint of suppressing the aggregation of the metal catalyst element, the measurement points satisfying the above (2) are preferably 2 to 48, more preferably 4 to 46, further preferably 7 to 43, and particularly preferably 10 to 40.

[0092] The total number of measurement points satisfying (1) and (2) is preferably 50. That is, all 50 measurement points preferably satisfy either (1) or (2).

[0093] In particular, the alumina-based composite oxide preferably also satisfies all of the following requirements (7) to (8):

[0094] (7) Among the 50 points, there are 10 or more measurement points where the aluminum oxide content is 50 mass % or more and 99 mass % or less and the content of the oxide of the element other than aluminum oxide is 1 mass % or more and 50 mass % or less;

[0095] (8) Among the 50 points, there are 10 or more measurement points where the aluminum oxide content is 1 mass % or more and less than 50 mass % and the content of the oxide of the element other than aluminum oxide is more than 50 mass % and less than 99 mass %.

[0096] From the viewpoint of suppressing the aggregation of the metal catalyst element, the difference between the maximum value and the minimum value of the alumina content at the 50 measurement points specified in (3) is preferably 21 or more, more preferably 23 or more, and even more preferably 25 or more.

[0097] From the viewpoint of inhibiting the degradation of the catalyst carrier (or inhibiting the agglomeration of the metal catalyst element), the difference between the maximum and minimum values ​​of the alumina content at the 50 measurement points specified in (3) is preferably less than 94, more preferably less than 92, and further preferably less than 90.

[0098] From the viewpoint of suppressing the aggregation of the metal catalyst element, the difference between the maximum and minimum values ​​of the alumina content at the 50 measurement points specified in (3) is preferably 21 to 94, more preferably 23 to 92, and even more preferably 25 to 90.

[0099] From the viewpoint of suppressing the aggregation of the metal catalyst element, the difference between the maximum value and the minimum value of the content of the oxide of the element other than aluminum oxide at the 50 measurement points specified in (4) is preferably 21 or more, more preferably 23 or more, and even more preferably 25 or more.

[0100] From the viewpoint of inhibiting the degradation of the catalyst carrier (or inhibiting the agglomeration of the metal catalyst elements), the difference between the maximum and minimum values ​​of the content of the oxide of elements other than aluminum oxide at the 50 measurement points specified in (4) is preferably less than 94, more preferably less than 92, and further preferably less than 90.

[0101] From the viewpoint of inhibiting the aggregation of metal catalyst elements, the difference between the maximum and minimum values ​​of the content of element oxides other than aluminum oxide at the 50 measurement points specified in (4) is preferably greater than 21 and less than 94, more preferably greater than 23 and less than 92, and further preferably greater than 25 and less than 90.

[0102] The alumina-based composite oxide also preferably satisfies all of the following requirements (5) to (6):

[0103] (5) Among the 50 points, at least one measurement point exists where the aluminum oxide content is 55 mass % to 99 mass % and the content of the oxide of the element other than aluminum oxide is 1 mass % to 45 mass %;

[0104] (6) Among the 50 points, there is at least one measurement point where the aluminum oxide content is 1 mass % to 45 mass % and the content of the element oxide other than aluminum oxide is 55 mass % to 99 mass %.

[0105] If the tertiary particles constituting the alumina-based composite oxide further satisfy the above-mentioned (5) to (6) in addition to the above-mentioned (1) to (4), aggregation of the metal catalyst element can be further suppressed.

[0106] From the viewpoint of suppressing the aggregation of the metal catalyst element, the number of measurement points satisfying the above-mentioned (5) is preferably 2 or more, more preferably 3 or more, and even more preferably 5 or more.

[0107] From the viewpoint of suppressing the aggregation of the metal catalyst element, the number of measurement points satisfying the above-mentioned (5) is preferably 48 points or less, more preferably 47 points or less, and even more preferably 45 points or less.

[0108] From the viewpoint of suppressing the aggregation of the metal catalyst element, the measurement points satisfying the above (5) preferably exist at least 2 and no more than 48 points, more preferably exist at least 3 and no more than 47 points, and even more preferably exist at least 5 and no more than 45 points.

[0109] From the viewpoint of suppressing the aggregation of the metal catalyst element, the number of measurement points satisfying the above-mentioned (6) is preferably 2 or more, more preferably 3 or more, and even more preferably 5 or more.

[0110] From the viewpoint of suppressing the aggregation of the metal catalyst element, the number of measurement points satisfying the above-mentioned (6) is preferably 48 points or less, more preferably 47 points or less, and even more preferably 45 points or less.

[0111] From the viewpoint of suppressing the aggregation of the metal catalyst element, the measurement points satisfying the above (6) preferably exist at least 2 and no more than 48 points, more preferably exist at least 3 and no more than 47 points, and even more preferably exist at least 5 and no more than 45 points.

[0112] In particular, the alumina-based composite oxide preferably also satisfies all of the following requirements (9) to (10):

[0113] (9) Among the 50 points, there are 5 or more measurement points where the aluminum oxide content is 55 mass % or more and 99 mass % or less and the content of the oxide of the element other than aluminum oxide is 1 mass % or more and 45 mass % or less;

[0114] (10) Among the 50 points, there are 5 or more measurement points where the aluminum oxide content is 1 mass % to 45 mass % and the content of the element oxide other than aluminum oxide is 55 mass % to 99 mass %.

[0115] The alumina-based composite oxide also preferably meets all of the following requirements (a) to (b):

[0116] (a) Among the 50 points, there is at least one measurement point where the aluminum oxide content is 60 mass % to 99 mass % and the content of the element oxide other than aluminum oxide is 1 mass % to 40 mass %;

[0117] (b) Among the 50 points, there is at least one measurement point where the aluminum oxide content is 1 mass % to 40 mass % and the content of the element oxide other than aluminum oxide is 60 mass % to 99 mass %.

[0118] In the tertiary particles constituting the alumina-based composite oxide, if the differences (a) to (b) are satisfied in addition to (1) to (6), aggregation of the metal catalyst element can be further suppressed.

[0119] From the viewpoint of suppressing the aggregation of the metal catalyst element, the measurement points satisfying the above condition (a) preferably exist at two or more points, more preferably exist at three or more points, and even more preferably exist at four or more points.

[0120] From the viewpoint of suppressing the aggregation of the metal catalyst element, the number of measurement points satisfying the above-mentioned (a) is preferably 48 or less, more preferably 47 or less, and even more preferably 46 or less.

[0121] From the viewpoint of suppressing aggregation of the metal catalyst element, the measurement points satisfying the above (a) preferably exist at least 2 and no more than 48 points, more preferably exist at least 3 and no more than 47 points, and even more preferably exist at least 4 and no more than 46 points.

[0122] From the viewpoint of suppressing the aggregation of the metal catalyst element, the measurement points satisfying the above condition (b) preferably exist at two or more points, more preferably exist at three or more points, and even more preferably exist at four or more points.

[0123] From the viewpoint of suppressing the aggregation of the metal catalyst element, the number of measurement points satisfying the above condition (b) is preferably 48 or less, more preferably 47 or less, and still more preferably 46 or less.

[0124] From the viewpoint of suppressing the aggregation of the metal catalyst element, the measurement points satisfying the above (b) preferably exist at least 2 and no more than 48 points, more preferably exist at least 3 and no more than 47 points, and even more preferably exist at least 4 and no more than 46 points.

[0125] The above (1) to (10) and the above (a) to (b) can be controlled according to a manufacturing method. Specifically, they can be controlled according to the following manufacturing method described below.

[0126] A method for producing an alumina-based composite oxide, comprising:

[0127] Step 1, adding acid to sodium aluminate to obtain hydrated alumina suspension A;

[0128] Step 2, preparing an aqueous solution B-1 containing an industrial salt of cerium and / or zirconium, and / or a suspension B-2 containing an industrial salt of cerium and / or zirconium;

[0129] Step 3, obtaining a precipitate of an aluminum composite precursor by mixing the suspension A with the aqueous solution B-1 and / or the suspension B-2; and

[0130] In step 4, the precipitate is heat-treated to obtain an alumina-based composite oxide.

[0131] <Particle size D 50 >

[0132] The particle size D of the alumina composite oxide 50 It is preferably 3.0 μm or more and 200 μm or less. 50 When the particle size D is less than 200 μm, no coarse particles will remain even when the particle size is pulverized to any particle size.50 When the particle size is 3.0 μm or more, differences in element distribution may occur in the same tertiary particle.

[0133] The particle size D 50 It is more preferably 3.5 μm or more, and even more preferably 4.0 μm or more. 50 It is more preferably 150 μm or less, and even more preferably 120 μm or less. 50 is a value obtained according to the method described in the embodiment.

[0134] <Particle size D 90 >

[0135] The particle size D of the alumina composite oxide 90 It is preferably 4.0 μm or more and 300 μm or less. 90 When the particle size D is less than 300 μm, no coarse particles will remain even when the particle size is pulverized to any particle size. 90 When the particle size is 4.0 μm or more, differences in element distribution may occur in the same tertiary particle.

[0136] The particle size D 90 It is more preferably 6.0 μm or more, and even more preferably 8.0 μm or more. 90 It is more preferably 250 μm or less, and even more preferably 220 μm or less. 90 is a value obtained according to the method described in the embodiment.

[0137] It should be noted that, during the measurement, the particle size D 50 In addition to tertiary particles, unagglomerated secondary particles may also be included, but the amount of unagglomerated secondary particles that may be included in the alumina-based composite oxide is extremely small. 50 It can be regarded as the particle size D of the tertiary particles. 50 .

[0138] The pore volume of the alumina-based composite oxide in the entire range of pore diameter distribution (pore diameter of 3 nm or more and less than 200 nm) determined by nitrogen adsorption / desorption method is preferably 0.10 mL / g or more and 1.0 mL / g or less.

[0139] When the pore volume is 0.10 mL / g or more, the metal catalyst element is also supported in the pores, and therefore segregation due to the unsupported metal catalyst element is less likely to occur.

[0140] When the pore volume is 1.0 mL / g or less, the aggregation of the secondary particles within the same tertiary particle becomes denser, and tertiary particles having different element distributions can be formed.

[0141] The pore volume is more preferably 0.15 mL / g or more, and further preferably 0.20 mL / g or more.

[0142] The pore volume is more preferably 0.90 mL / g or less, and further preferably 0.80 mL / g or less.

[0143] The pore volume is more preferably 0.15 mL / g to 0.90 mL / g, and even more preferably 0.20 mL / g to 0.80 mL / g.

[0144] [Rh particle size after Rh loading and heat treatment]

[0145] When the alumina content is 50 mass % or more and 80 mass % or less, the Rh particle size of the alumina-based composite oxide after supporting Rh under the following loading conditions and performing heat treatment under the following heat treatment conditions is preferably 90 μm or less.

[0146] When the alumina content is 30 mass % or more and less than 50 mass %, the Rh particle size of the alumina-based composite oxide after Rh is supported under the following loading conditions and heat-treated under the following heat treatment conditions is preferably 95 μm or less.

[0147] When the alumina content is 15 mass % or more and less than 30 mass %, the Rh particle size of the alumina-based composite oxide after Rh is supported under the following loading conditions and heat-treated under the following heat treatment conditions is preferably 110 μm or less.

[0148] When the Rh particle size after the heat treatment is equal to or smaller than the above particle size, it can be said that the aggregation of the catalyst metal element when exposed to a high temperature region for a long time can be further suppressed.

[0149] <Load conditions>

[0150] An 8% Rh nitrate solution containing 2% by mass of Rh was impregnated in 100% by mass of the alumina-based composite oxide, dried at 100° C., and then fired at 500° C. for 5 hours to obtain a Rh-supported powder.

[0151] <Heat treatment conditions>

[0152] The obtained Rh-loaded powder was heat-treated in an air environment at 1200° C. for 12 hours to obtain a heat-treated sample.

[0153] When the aluminum oxide content is 50 mass % or more and 80 mass % or less, the Rh particle size is more preferably 85 μm or less, and further preferably 80 μm or less.

[0154] When the aluminum oxide content is 30 mass % or more and less than 50 mass %, the Rh particle size is more preferably 90 μm or less, and further preferably 85 μm or less.

[0155] When the aluminum oxide content is 15 mass % or more and less than 30 mass %, the Rh particle size is more preferably 105 μm or less, and further preferably 100 μm or less.

[0156] The Rh particle size is irrelevant to the aluminum oxide content, and the smaller the better, for example, 20 μm or more, 30 μm or more, etc.

[0157] The Rh particle size is a value obtained according to the method described in Examples.

[0158] The alumina-based composite oxide contains alumina. Since the alumina-based composite oxide contains alumina, it can be preferably used as a catalyst carrier.

[0159] In the composition analysis obtained by X-ray fluorescence method, the content of the aluminum oxide is preferably 15 mass % or more and 80 mass % or less. When the content of the aluminum oxide is 15 mass % or more and 80 mass % or less, thermal degradation of the catalyst can be suppressed, so when the metal catalyst element is supported on the aluminum oxide composite oxide, aggregation of the metal catalyst element can be further suppressed.

[0160] The content of aluminum oxide is more preferably 20% by mass or more, and even more preferably 25% by mass or more. Furthermore, the content of aluminum oxide is more preferably 75% by mass or less, and even more preferably 70% by mass or less.

[0161] The alumina-based composite oxide contains ceria and / or zirconia. Since the alumina-based composite oxide contains ceria and / or zirconia, it can be preferably used as a catalyst carrier.

[0162] In the composition analysis obtained by X-ray fluorescence method, the content of the cerium oxide and / or zirconium oxide is preferably 0.1 mass % or more and 85 mass % or less. Since the cerium oxide and / or zirconium oxide is used as a promoter, when the content of the cerium oxide and / or zirconium oxide is 0.1 mass % or more, it is suitable for use as a catalyst carrier. In addition, when the content of the cerium oxide and / or zirconium oxide is 85 mass % or less, thermal degradation can be suppressed.

[0163] When the alumina-based composite oxide contains cerium oxide, the content of the cerium oxide is preferably 1% by mass or more and 80% by mass or less in a composition analysis by an X-ray fluorescence method.

[0164] The content of cerium oxide is more preferably 3% by mass or more, and further preferably 6% by mass or more. Furthermore, the content of cerium oxide is more preferably 75% by mass or less, and further preferably 70% by mass or less.

[0165] When the alumina-based composite oxide contains zirconium oxide, the content of the zirconium oxide is preferably 1% by mass or more and 75% by mass or less in a composition analysis by an X-ray fluorescence method.

[0166] The content of zirconium oxide is more preferably 5% by mass or more, and even more preferably 10% by mass or more. Furthermore, the content of zirconium oxide is more preferably 70% by mass or less, and even more preferably 65% ​​by mass or less.

[0167] In the alumina-based composite oxide, when cerium oxide and zirconium oxide are simultaneously contained, in a composition analysis obtained by an X-ray fluorescence method, when the entire alumina-based composite oxide is set to 100 mass%, the total content of alumina, cerium oxide and zirconium oxide is preferably 70 mass% or more and 98 mass% or less. By setting the total content of alumina, cerium oxide and zirconium oxide to 70 mass% or more and 98 mass% or less, it can be more preferably used as a catalyst carrier.

[0168] When cerium oxide and zirconium oxide are both contained, in the composition analysis obtained by X-ray fluorescence method, when the entire aluminum oxide-based composite oxide is set to 100 mass%, the total content of aluminum oxide, cerium oxide and zirconium oxide is more preferably 75 mass% or more, and further preferably 80 mass% or more. When cerium oxide and zirconium oxide are both contained, when the entire aluminum oxide-based composite oxide is set to 100 mass%, the total content of aluminum oxide, cerium oxide and zirconium oxide is more preferably 97 mass% or less, and further preferably 96 mass% or less.

[0169] In the alumina-based composite oxide, when cerium oxide is included but zirconium oxide is not included, in a composition analysis obtained by an X-ray fluorescence method, when the entire alumina-based composite oxide is set to 100 mass%, the total content of alumina and cerium oxide is preferably 70 mass% or more and 96 mass% or less. By setting the total content of alumina and cerium oxide to 70 mass% or more and 96 mass% or less, it can be more preferably used as a catalyst carrier.

[0170] When cerium oxide is included but zirconium oxide is not included, when the entire aluminum oxide composite oxide is set to 100 mass%, the total content of aluminum oxide and cerium oxide is more preferably 75 mass% or more, and more preferably 80 mass% or more. When cerium oxide is included but zirconium oxide is not included, when the entire aluminum oxide composite oxide is set to 100 mass%, the total content of aluminum oxide and cerium oxide is more preferably 95 mass% or less, and more preferably 94 mass% or less.

[0171] In the alumina-based composite oxide, when zirconium oxide is included but cerium oxide is not included, in a composition analysis obtained by an X-ray fluorescence method, when the entire alumina-based composite oxide is set to 100 mass%, the total content of alumina and zirconium oxide is preferably 70 mass% to 96 mass%. By setting the total content of alumina and zirconium oxide to 70 mass% to 96 mass%, it can be more preferably used as a catalyst carrier.

[0172] When zirconium oxide is included but cerium oxide is not included, when the entire aluminum oxide composite oxide is set to 100 mass%, the total content of aluminum oxide and zirconium oxide is more preferably 75 mass% or more, and further preferably 80 mass% or more. When zirconium oxide is included but cerium oxide is not included, when the entire aluminum oxide composite oxide is set to 100 mass%, the total content of aluminum oxide and zirconium oxide is more preferably 95 mass% or less, and further preferably 94 mass% or less.

[0173] As oxides other than aluminum oxide, cerium oxide, and zirconium oxide, the aluminum oxide composite oxide preferably includes at least one oxide of a rare earth element other than cerium and promethium. When the oxide of a rare earth element other than cerium and promethium is included, the aggregation of the metal catalyst element can be further suppressed.

[0174] Among oxides of rare earth elements other than cerium and promethium, the alumina-based composite oxide preferably contains oxides of La, Nd, Pr, and Y. When the alumina-based composite oxide contains oxides of La, Nd, Pr, and Y, aggregation of metal catalyst elements can be further suppressed.

[0175] When the oxide of the rare earth element other than cerium and promethium is contained, in the composition analysis obtained by X-ray fluorescence method, when the whole of the alumina-based composite oxide is set to 100 mass%, the content of the oxide of the rare earth element other than cerium and promethium is preferably 2 mass% or more and 20 mass% or less. When the content of the oxide of the rare earth element other than cerium and promethium is 2 mass% or more and 20 mass% or less, the aggregation of the metal catalyst element can be further suppressed.

[0176] In the composition analysis obtained by X-ray fluorescence, when the entire alumina-based composite oxide is set to 100 mass%, the content of oxides of rare earth elements other than cerium and promethium is more preferably 3 mass% or more, and further preferably 4 mass% or more. In the composition analysis obtained by X-ray fluorescence, when the entire alumina-based composite oxide is set to 100 mass%, the content of oxides of rare earth elements other than cerium and promethium is more preferably 18 mass% or less, and further preferably 16 mass% or less.

[0177] The alumina composite oxide may include one or more selected from the following oxides: (A) an oxide of at least one element selected from the group consisting of In, Si, Sn, Bi, P, and Zn; (B) a transition metal oxide (excluding oxides of rare earth elements); and (C) an alkaline earth metal oxide. The components (A) to (C) are hereinafter referred to as "other oxides".

[0178] The transition metal oxide may be, for example, one or more oxides selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Nb, Mo, Ta, and W. In addition, the alkaline earth metal oxide may be one or more oxides selected from the group consisting of Mg, Ca, Sr, and Ba.

[0179] When the alumina-based composite oxide includes the other oxides, when the alumina-based composite oxide as a whole is set to 100 mass%, the content of the other oxides is preferably 0.1 mass% or more and 30 mass% or less. When the alumina-based composite oxide as a whole is set to 100 mass%, the content of the other oxides is more preferably 0.3 mass% or more, and further preferably 0.5 mass% or more. When the alumina-based composite oxide as a whole is set to 100 mass%, the content of the other oxides is more preferably 25 mass% or less, and further preferably 20 mass% or less.

[0180] The preferred composition ratio of the alumina-based composite oxide may be a combination not exceeding 100% by mass in total (a combination of 100% by mass in total) as shown below. (1)

[0182] Alumina: 40% or more but less than 80%

[0183] Zirconia: 1% to 30%

[0184] Cerium oxide: 1% to 30%

[0185] Oxides of rare earth elements other than cerium and promethium: 1% to 15%

[0186] Other oxides: 0% or more but less than 10% (2)

[0188] Alumina: 20% or more but less than 60%

[0189] Zirconia: 20% or more but less than 70%

[0190] Cerium oxide: 1% to 40%

[0191] Oxides of rare earth elements other than cerium and promethium: 1% to 15%

[0192] Other oxides: 0% or more but less than 10% (3)

[0194] Alumina: 20% or more but less than 60%

[0195] Zirconia: 20% or more but less than 75%

[0196] Cerium oxide: 0% to 30%

[0197] Oxides of rare earth elements other than cerium and promethium: 1% to 15%

[0198] Other oxides: 0% or more but less than 10% (4)

[0200] Alumina: 20% or more but less than 60%

[0201] Zirconia: 0% to 20%

[0202] Cerium oxide: 20% or more but less than 70%

[0203] Oxides of rare earth elements other than cerium and promethium: 5% to 20%

[0204] Other oxides: 0% or more but less than 20% (5)

[0206] Alumina: 20% or more but less than 60%

[0207] Zirconia: 10% to 60%

[0208] Cerium oxide: 0% to 40%

[0209] Oxides of rare earth elements other than cerium and promethium: 1% to 15%

[0210] Other oxides: more than 1% but less than 20%

[0211] The use of the alumina-based composite oxide is not particularly limited, but it is preferably used as a catalyst carrier, and particularly preferably used as a catalyst carrier for an exhaust gas-purifying catalyst (exhaust gas-purifying catalyst carrier).

[0212] The metal catalyst element supported on the alumina-based composite oxide is not particularly limited, and is preferably, for example, Rh, Pt, Pd, Au, Ru, Ag, Ni, Co, Mn, Cu, or Fe.

[0213] It should be noted that the metal catalyst element supported on the alumina-based composite oxide may overlap with the element contained in the alumina-based composite oxide. For example, when the alumina-based composite oxide contains Fe, Fe may also be used as the metal catalyst element supported on the alumina-based composite oxide.

[0214] [Method for producing alumina-based composite oxide]

[0215] Hereinafter, an example of the method for producing an alumina-based composite oxide will be described. However, the method for producing an alumina-based composite oxide of the present invention is not limited to the following example.

[0216] The method for producing an alumina-based composite oxide according to the present embodiment includes:

[0217] Step 1, adding acid to sodium aluminate to obtain hydrated alumina suspension A;

[0218] Step 2, preparing an aqueous solution B-1 containing an industrial salt of cerium and / or zirconium, and / or a suspension B-2 containing an industrial salt of cerium and / or zirconium;

[0219] Step 3, obtaining a precipitate of an aluminum composite precursor by mixing the suspension A with the aqueous solution B-1 and / or the suspension B-2; and

[0220] In step 4, the precipitate is heat-treated to obtain an alumina-based composite oxide.

[0221] Hereinafter, each step of the method for producing the alumina-based composite oxide according to the present embodiment will be described.

[0222] (1) Process 1

[0223] In step 1, an acid is added to sodium aluminate (NaAl(OH)4) to obtain a hydrated alumina suspension A.

[0224] The sodium aluminate may be in the form of liquid or powder. When gas is used as the acid, the sodium aluminate is preferably in the form of liquid.

[0225] When a liquid is used as the sodium aluminate, the concentration of the sodium aluminate is preferably 1 mass % or more and 20 mass % or less based on aluminum dioxide.

[0226] The temperature of the sodium aluminate is preferably 20° C. or higher and 90° C. or lower. The temperature of the sodium aluminate is more preferably 25° C. or higher, and even more preferably 30° C. or higher.

[0227] The temperature of the sodium aluminate is more preferably 85° C. or lower, and further preferably 80° C. or lower.

[0228] By setting the temperature of the sodium aluminate within the numerical range, it is easy to obtain an alumina-based composite oxide having an element distribution that satisfies the above (1) to (8). Specifically, the higher the temperature of the sodium aluminate, the greater the difference in element distribution within the range that satisfies the above (1) to (6).

[0229] The acid added to the sodium aluminate may be in the form of a gas (gaseous state) or a liquid (solution). The acid may specifically be carbon dioxide, hydrochloric acid, nitric acid, sulfuric acid, carboxylic acid, etc. Among them, carbon dioxide gas is preferred from the viewpoint of less impurities.

[0230] When carbon dioxide gas is blown into the sodium aluminate, the flow rate of carbon dioxide gas is preferably 1.7×10 -7 m 3 / s or more 1.7×10 -5 m 3 / s or less, more preferably 5.0×10 -7 m 3 / s or more 5.0×10 -6 m 3 / s or less.

[0231] When carbon dioxide gas is blown into the sodium aluminate, the duration of blowing carbon dioxide gas is preferably from 6 hours to 48 hours, and more preferably from 12 hours to 36 hours.

[0232] By blowing carbon dioxide gas into the sodium aluminate under the above conditions, a suitable suspension A can be obtained.

[0233] (2) Process 2

[0234] In step 2, an aqueous solution B-1 containing an industrial salt of cerium and / or zirconium and / or a suspension B-2 containing an industrial salt of cerium and / or zirconium are prepared. In step 2, only the aqueous solution B-1 containing an industrial salt of cerium and / or zirconium may be prepared, only the suspension B-2 containing an industrial salt of cerium and / or zirconium may be prepared, or both the aqueous solution B-1 containing an industrial salt of cerium and / or zirconium and the suspension B-2 containing an industrial salt of cerium and / or zirconium may be prepared.

[0235] The aqueous solution B-1 is obtained by mixing various industrial salts described below.

[0236] The suspension B-2 is obtained by heat treating the aqueous solution B-1. The temperature of the heat treatment is preferably 140°C to 250°C, more preferably 160°C to 200°C. The duration of the heat treatment is preferably 1 hour to 10 hours, preferably 2 hours to 5 hours. Compared with the case of using the aqueous solution B-1, when the suspension B-2 is used, the difference in element distribution tends to be greater within the range of satisfying the above (1) to (6).

[0237] When the aqueous solution B-1 and the suspension B-2 are used simultaneously, the aqueous solution B-1 and the suspension B-2 may be prepared simultaneously and mixed for use.

[0238] The industrial salt containing cerium may be, for example, at least one of cerium nitrate, cerium chloride, cerium acetate, etc. Among them, cerium nitrate, which is a nitrate system, is preferred.

[0239] The industrial salt containing zirconium may be at least one of zirconium oxynitrate, zirconium oxychloride, zirconium nitrate, etc., as long as it can provide zirconium ions. Among them, zirconium oxynitrate in the form of a nitrate is preferred.

[0240] The aqueous solution B-1 and the suspension B-2 may contain industrial salt, and the industrial salt contains rare earth elements other than cerium and promethium.

[0241] The rare earth element other than cerium and promethium may be at least one of Sc, Y, La, Nd, Pr, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm and Lu. Among them, Y, La, Nd and Pr are preferred.

[0242] In addition to the above-mentioned elements, the aqueous solution B-1 and the suspension B-2 may also contain one or more elements selected from the following elements: (A) at least one element selected from the group consisting of In, Si, Sn, Bi, P, and Zn; (B) transition metal elements (excluding rare earth elements and precious metal elements); and (C) alkaline earth metal elements.

[0243] The raw materials of rare earth elements, transition metal elements (except rare earth elements and noble metal elements), alkaline earth metals, In, Si, Sn, Bi and P are not particularly limited as long as they are water-soluble compounds. They may be nitrates, sulfates, acetates, chlorides, bromides, etc., but industrial salts are preferably nitrates from the viewpoint of being able to suppress residual impurities. The purity of these raw materials is preferably 95% or more, more preferably 98% or more.

[0244] The solvent used to prepare the aqueous solution B-1 may be appropriately selected according to the type of industrial salt, etc., and water (pure water, ion-exchanged water, etc., the same applies hereinafter) is usually preferably used.

[0245] The concentration of the metal salt in the aqueous solution B-1 is preferably 1% or more and 15% or less in terms of oxide. By setting the concentration to be 1% or more, the concentration can be made thicker to a certain extent, and the treatment time is more appropriate. In addition, by setting the concentration to be 15% or less, the viscosity increase during the neutralization process can be suppressed, and the composite can be smoothly carried out.

[0246] (3) Process 3

[0247] In step 3, the suspension A and the aqueous solution B-1 and / or the suspension B-2 are mixed to obtain a precipitate of an aluminum-based composite precursor.

[0248] Specifically, in step 3, first, the suspension A obtained in step 1 and the aqueous solution B-1 and / or suspension B-2 obtained in step 2 are mixed, and a base is added to obtain a precursor precipitate of an alumina-based composite oxide. The mixing is not particularly limited, but from the viewpoint of productivity such as filterability in the next step, it is preferred that the aqueous solution B-1 and / or suspension B-2 prepared in step 2 be added to the suspension A prepared in step 1.

[0249] The alkali is not limited, and for example, ammonium hydroxide, ammonium hydrogen carbonate, sodium hydroxide, potassium hydroxide, etc. can be used. Among them, sodium hydroxide is preferred from the viewpoint of industrial cost.

[0250] The amount of the base added is not particularly limited as long as the precursor precipitate of the aluminum oxide composite oxide can be generated as a salt precipitate. Usually, the pH added to the solution is 8.0 to 11.0, preferably 9.0 to 10.0.

[0251] Next, the generated precipitate of the aluminum-based composite precursor is recovered by a solid-liquid separation method. The solid-liquid separation method can be carried out by a known method such as filtration, centrifugal separation, and decantation.

[0252] After recovery, the obtained alumina-based composite hydrate is preferably washed with water to remove attached impurities, if necessary.

[0253] It should be noted that the obtained aluminum oxide composite hydrate may be further dried as required. The drying method may be a known method, such as natural drying, heating drying, etc. Alternatively, if necessary, a pulverization treatment, a classification treatment, etc. may be performed after the drying treatment.

[0254] (4) Process 4

[0255] In step 4, the precipitate (recovered product) is heat-treated to obtain an alumina-based composite oxide.

[0256] The heat treatment temperature is not particularly limited, and is usually performed in the range of 500° C. to 1200° C. for 2 hours to 10 hours. The heat treatment atmosphere is not particularly limited, and may be air or oxidizing atmosphere.

[0257] It should be noted that the alumina-based composite oxide obtained by heat treatment may be pulverized as needed. The pulverization is not particularly limited, and a common pulverizer such as a planetary mill, a ball mill, a hammer mill, or a jet mill may be used for pulverization.

[0258] In the above-mentioned method for producing alumina-based composite oxides, by mixing the hydrated alumina suspension A and the aqueous solution B-1 and / or suspension B-2 containing industrial salts of cerium and / or zirconium, the precursors of cerium oxide and zirconium oxide can be set on the surface and / or inside of the hydrated alumina. Thus, the secondary alumina particles containing cerium oxide and zirconium oxide and the secondary alumina particles containing cerium oxide and zirconium oxide can coexist in the tertiary particles of the alumina-based composite oxide. In addition, by controlling the aggregation of the hydrated alumina and the precursors of cerium oxide and zirconium oxide, the element distribution in the tertiary particles of the composite oxide can be controlled.

[0259] By such a production method, an alumina-based composite oxide having the above-mentioned properties (1) to (8) can be obtained.

[0260] Example

[0261] The present invention is described in detail below with reference to the examples, but the present invention is not limited to the following examples as long as it does not exceed the gist of the present invention. It should be noted that the alumina-based composite oxides obtained in the examples and comparative examples contain 1 to 3% by mass of hafnium (calculated by the following formula (X)) relative to zirconium as an inevitable impurity:

[0262] <Formula (X)>

[0263] ([mass of hafnium] / ([mass of zirconium]+[mass of hafnium]))×100(%).

[0264] The maximum and minimum values ​​of the content of each component shown in the following examples are irrelevant to the contents of other components and should be regarded as the preferred minimum and preferred maximum values ​​of the present invention.

[0265] Furthermore, the maximum and minimum values ​​of the measured values ​​shown in the following examples have nothing to do with the content (composition) of each component, and should be regarded as the preferred minimum and maximum values ​​of the present invention.

[0266] [Preparation of Alumina-Based Composite Oxide]

[0267] (Example 1)

[0268] Sodium aluminate (Asada Chemical Industry, #2019, 78 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0269] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 8 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 8 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing an aqueous nitrate solution (aqueous solution B-1).

[0270] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0271] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized by a hammer mill to obtain an alumina composite oxide of Example 1.

[0272] (Example 2)

[0273] Sodium aluminate (Asada Chemical Industry, #2019, 78 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 70°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0274] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 8 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 8 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing an aqueous nitrate solution (aqueous solution B-1).

[0275] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0276] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized by a hammer mill to obtain an alumina composite oxide of Example 2.

[0277] (Example 3)

[0278] Sodium aluminate (Asada Chemical Industry, #2019, 78 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0279] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 8 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 8 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing an aqueous nitrate solution (aqueous solution B-1).

[0280] This aqueous solution B-1 was maintained at 180° C. for 2 hours in an autoclave to prepare a composite metal salt suspension (suspension B-2).

[0281] The suspension A and the suspension B-2 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0282] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized by a hammer mill to obtain an alumina composite oxide of Example 3.

[0283] (Example 4)

[0284] Sodium aluminate (Asada Chemical Industry, #2019, 69 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 70°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0285] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 15 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 10 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), praseodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of praseodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing an aqueous nitrate solution (aqueous solution B-1).

[0286] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0287] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized by a hammer mill to obtain an alumina composite oxide of Example 4.

[0288] (Example 5)

[0289] Sodium aluminate (Asada Chemical Industry, #2019, 54 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 35°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 -6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0290] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 20 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 10 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of neodymium oxide), praseodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of praseodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0291] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0292] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized by a hammer mill to obtain an alumina composite oxide of Example 5.

[0293] (Example 6)

[0294] Sodium aluminate (Asada Chemical Industry, #2019, 54 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0295] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 20 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 10 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of neodymium oxide), praseodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of praseodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0296] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0297] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized by a hammer mill to obtain an alumina composite oxide of Example 6.

[0298] (Example 7)

[0299] Sodium aluminate (Asada Chemical Industry, #2019, 54 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 70°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0300] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 20 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 10 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of neodymium oxide), praseodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of praseodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0301] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0302] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized by a hammer mill to obtain an alumina composite oxide of Example 7.

[0303] (Example 8)

[0304] Sodium aluminate (Asada Chemical Industry, #2019, 42 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0305] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 50 g in terms of zirconium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0306] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0307] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was crushed by a hammer mill to obtain an alumina composite oxide of Example 8.

[0308] (Example 9)

[0309] Sodium aluminate (Asada Chemical Industry, #2019, 42 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 70°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0310] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 50 g in terms of zirconium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0311] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0312] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized by a hammer mill to obtain an alumina composite oxide of Example 9.

[0313] (Example 10)

[0314] Sodium aluminate (Asada Chemical Industry, #2019, 42 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0315] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 50 g in terms of zirconium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0316] This aqueous solution B-1 was maintained at 180° C. for 2 hours in an autoclave to prepare a composite metal salt suspension (suspension B-2).

[0317] The suspension A and the suspension B-2 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0318] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized by a hammer mill to obtain an alumina composite oxide of Example 10.

[0319] (Example 11)

[0320] Sodium aluminate (Asada Chemical Industry, #2019, 42 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0321] Cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 50 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing an aqueous nitrate solution (aqueous solution B-1).

[0322] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0323] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 11.

[0324] (Example 12)

[0325] Sodium aluminate (Asada Chemical Industry, #2019, 42 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 70°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0326] Cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 50 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing an aqueous nitrate solution (aqueous solution B-1).

[0327] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0328] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 12.

[0329] (Example 13)

[0330] Sodium aluminate (Asada Chemical Industry, #2019, 42 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0331] Cerium (IV) diammonium nitrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 50 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing an aqueous nitrate solution (aqueous solution B-1).

[0332] This aqueous solution B-1 was maintained at 180° C. for 2 hours in an autoclave to prepare a composite metal salt suspension (suspension B-2).

[0333] The suspension A and the suspension B-2 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0334] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 13.

[0335] (Example 14)

[0336] Sodium aluminate (Asada Chemical Industry, #2019, 30 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 70°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0337] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 44 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0338] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0339] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 14.

[0340] (Example 15)

[0341] Sodium aluminate (Asada Chemical Industry, #2019, 30 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0342] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 44 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0343] This aqueous solution B-1 was maintained at 180° C. for 2 hours in an autoclave to prepare a composite metal salt suspension (suspension B-2).

[0344] The suspension A and the suspension B-2 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0345] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized by a hammer mill to obtain an alumina composite oxide of Example 15.

[0346] (Example 16)

[0347] Sodium aluminate (Asada Chemical Industry, #2019, 30 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0348] Zirconium oxychloride octahydrate (Mizuwa Chemical, special grade reagent, 44 g in terms of zirconium oxide) was dissolved in ion exchange water, and then adjusted to an acid concentration of 0.67 N and a ZrO2 concentration of 4 wt / vol% using 35% hydrochloric acid and ion exchange water. The temperature of the aqueous solution was adjusted to 120°C and the pressure was adjusted to 2×10 5 After Pa, 650 g of a 5% sodium sulfate aqueous solution was added and the mixture was kept for another 15 minutes. Then, the mixture was cooled to room temperature to obtain a slurry containing basic zirconium sulfate.

[0349] Next, cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide) were added to the slurry containing basic zirconium sulfate, and a 25% sodium hydroxide aqueous solution was added until the pH reached 9, thereby preparing a composite metal salt suspension (suspension B). Suspension A and suspension B were mixed to obtain a precursor precipitate of an aluminum oxide-based composite oxide.

[0350] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized by a hammer mill to obtain an alumina composite oxide of Example 16.

[0351] (Example 17)

[0352] Sodium aluminate (Asada Chemical Industry, #2019, 20 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0353] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 60 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 10 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0354] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0355] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized by a hammer mill to obtain an alumina composite oxide of Example 17.

[0356] (Example 18)

[0357] Sodium aluminate (Asada Chemical Industry, #2019, 20 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 70°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0358] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 60 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 10 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0359] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0360] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 18.

[0361] (Example 19)

[0362] Sodium aluminate (Asada Chemical Industry, #2019, 20 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0363] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 70 g in terms of zirconium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0364] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0365] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 19.

[0366] (Example 20)

[0367] Sodium aluminate (Asada Chemical Industry, #2019, 20 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 70°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0368] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 70 g in terms of zirconium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0369] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0370] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 20.

[0371] (Example 21)

[0372] Sodium aluminate (Asada Chemical Industry, #2019, 20 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0373] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 70 g in terms of zirconium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0374] This aqueous solution B-1 was maintained at 180° C. for 2 hours in an autoclave to prepare a composite metal salt suspension (suspension B-2).

[0375] The suspension A and the suspension B-2 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0376] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 21.

[0377] (Example 22)

[0378] Sodium aluminate (Asada Chemical Industry, #2019, 20 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0379] Cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 70 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing an aqueous nitrate solution (aqueous solution B-1).

[0380] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0381] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 22.

[0382] (Example 23)

[0383] Sodium aluminate (Asada Chemical Industry, #2019, 20 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 70°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0384] Cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 70 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing an aqueous nitrate solution (aqueous solution B-1).

[0385] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0386] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 23.

[0387] (Example 24)

[0388] Sodium aluminate (Asada Chemical Industry, #2019, 15 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0389] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 59 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing an aqueous nitrate solution (aqueous solution B-1).

[0390] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0391] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 24.

[0392] (Example 25)

[0393] Sodium aluminate (Asada Chemical Industry, #2019, 15 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 70°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0394] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 59 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing an aqueous nitrate solution (aqueous solution B-1).

[0395] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0396] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 25.

[0397] (Example 26)

[0398] Sodium aluminate (Asada Chemical Industry, #2019, 30 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0399] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 40 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide), and titanium (IV) tetrachloride (Wako Pure Chemical Industries, Ltd., 4.0 g in terms of titanium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing an aqueous nitrate solution (aqueous solution B-1).

[0400] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0401] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 26.

[0402] (Example 27)

[0403] Sodium aluminate (Asada Chemical Industry, #2019, 30 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0404] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 40 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide), and monoammonium phosphate (Wako Chemical Industries, Ltd., special grade reagent, 4.0 g in terms of phosphate) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing an aqueous nitrate solution (aqueous solution B-1).

[0405] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0406] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 27.

[0407] (Example 28)

[0408] Sodium aluminate (Asada Chemical Industry, #2019, 30 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0409] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 40 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide), and fumed silica AEROSIL (Japan AEROSIL, 4.0 g in terms of silicon oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0410] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0411] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 28.

[0412] (Example 29)

[0413] Sodium aluminate (Asada Chemical Industry, #2019, 30 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0414] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 40 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide), and ammonium metatungstate hydrate (Wako Reagent, 4.0 g in terms of tungsten oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0415] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0416] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 29.

[0417] (Example 30)

[0418] Sodium aluminate (Asada Chemical Industry, #2019, 30 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0419] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 40 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide), and magnesium nitrate hexahydrate (Wako Chemical Industries, Ltd., special grade reagent, 4.0 g in terms of magnesium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0420] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0421] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 30.

[0422] (Example 31)

[0423] Sodium aluminate (Asada Chemical Industry, #2019, 30 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0424] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 40 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide), and calcium nitrate hexahydrate (Wako Chemical Industries, Ltd., special grade reagent, 4.0 g in terms of calcium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0425] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0426] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 31.

[0427] (Example 32)

[0428] Sodium aluminate (Asada Chemical Industry, #2019, 30 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0429] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 40 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide), and strontium nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4.0 g in terms of strontium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing an aqueous nitrate solution (aqueous solution B-1).

[0430] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0431] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 32.

[0432] (Example 33)

[0433] Sodium aluminate (Asada Chemical Industry, #2019, 30 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0434] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 40 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide), and barium nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4.0 g in terms of barium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0435] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0436] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 33.

[0437] (Example 34)

[0438] Sodium aluminate (Asada Chemical Industry, #2019, 30 g in terms of alumina) was diluted with ion exchange water to a concentration of 5% oxide equivalent, heated to 50°C, and injected with a gas injection tube with a filter plate at a flow rate of 100 sccm (1.7 × 10 - 6 m 3 / s) was blown into carbon dioxide gas for 24 hours and maintained, thereby preparing a hydrated aluminum oxide suspension (suspension A).

[0439] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 43 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide), and iron (III) nitrate nonahydrate (Wako Chemical Industries, Ltd., special grade reagent, 1.0 g in terms of iron oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution (aqueous solution B-1).

[0440] The suspension A and the aqueous solution B-1 were mixed, and a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of an alumina-based composite oxide.

[0441] Next, the precursor precipitate was recovered and washed by solid-liquid separation, and the solid portion was fired in an electric furnace at 900° C. for 5 hours in the air to obtain an alumina composite oxide. The alumina composite oxide was pulverized with a hammer mill to obtain an alumina composite oxide of Example 34.

[0442] (Comparative Example 1)

[0443] Aluminum nitrate nonahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 78 g in terms of aluminum dioxide), zirconium oxynitrate (Mitsuwa Chemical Industry, special grade reagent, 8 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 8 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 3%, thereby preparing an aqueous nitrate solution.

[0444] Next, 400 g of ammonium bicarbonate was dissolved in 7600 g of ion exchange water to prepare a 5% ammonium bicarbonate aqueous solution. Next, the nitrate aqueous solution was added to the ammonium bicarbonate aqueous solution to obtain a precursor precipitate of an alumina-based composite oxide.

[0445] Next, the precipitate was recovered and washed by solid-liquid separation. The solid portion was fired in an electric furnace at 900° C. for 5 hours in the atmosphere to obtain an alumina composite oxide. The alumina composite oxide was crushed by a hammer mill to obtain the alumina composite oxide of Comparative Example 1.

[0446] (Comparative Example 2)

[0447] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 8 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 8 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution. After the aqueous solution was kept at 180° C. for 2 hours in an autoclave, a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of a cerium oxide-zirconia composite oxide.

[0448] Next, the precipitate was recovered and washed by solid-liquid separation. The solid portion was fired in an electric furnace at 900° C. for 5 hours in the atmosphere to obtain a cerium oxide-zirconia composite oxide. The cerium oxide and zirconium oxide composite oxide were mixed with aluminum oxide (Sumitomo Chemical, AKP-G07, 78 g in terms of aluminum dioxide) and crushed with a hammer mill to obtain an aluminum oxide composite oxide of Comparative Example 2.

[0449] (Comparative Example 3)

[0450] Aluminum nitrate nonahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 69 g in terms of aluminum dioxide), zirconium oxynitrate (Mitsuwa Chemical Industry, special grade reagent, 15 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 10 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), praseodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of praseodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 3%, thereby preparing an aqueous nitrate solution.

[0451] Next, 400 g of ammonium bicarbonate was dissolved in 7600 g of ion exchange water to prepare a 5% ammonium bicarbonate aqueous solution. Next, the nitrate aqueous solution was added to the ammonium bicarbonate aqueous solution to obtain a precursor precipitate of an alumina-based composite oxide.

[0452] Next, the precipitate was recovered and washed by solid-liquid separation. The solid portion was fired in an electric furnace at 900° C. for 5 hours in the atmosphere to obtain an alumina composite oxide. The alumina composite oxide was crushed by a hammer mill to obtain an alumina composite oxide of Comparative Example 3.

[0453] (Comparative Example 4)

[0454] Aluminum nitrate nonahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 54 g in terms of aluminum dioxide), zirconium oxynitrate (Mitsuwa Chemical Industry, special grade reagent, 20 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 10 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of neodymium oxide), praseodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of praseodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion-exchanged water until the oxide equivalent reached 3%, thereby preparing an aqueous nitrate solution.

[0455] Next, 400 g of ammonium bicarbonate was dissolved in 7600 g of ion exchange water to prepare a 5% ammonium bicarbonate aqueous solution. Next, the nitrate aqueous solution was added to the ammonium bicarbonate aqueous solution to obtain a precursor precipitate of an alumina-based composite oxide.

[0456] Next, the precipitate was recovered and washed by solid-liquid separation. The solid portion was fired in an electric furnace at 900° C. for 5 hours in the atmosphere to obtain an alumina composite oxide. The alumina composite oxide was crushed by a hammer mill to obtain an alumina composite oxide of Comparative Example 4.

[0457] (Comparative Example 5)

[0458] Aluminum nitrate nonahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 42 g in terms of aluminum dioxide), zirconium oxynitrate (Mitsuwa Chemical Industry, special grade reagent, 50 g in terms of zirconium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 3%, thereby preparing an aqueous nitrate solution.

[0459] Next, 400 g of ammonium bicarbonate was dissolved in 7600 g of ion exchange water to prepare a 5% ammonium bicarbonate aqueous solution. Next, the nitrate aqueous solution was added to the ammonium bicarbonate aqueous solution to obtain a precursor precipitate of an alumina-based composite oxide.

[0460] Next, the precipitate was recovered and washed by solid-liquid separation. The solid portion was fired in an electric furnace at 900° C. for 5 hours in the atmosphere to obtain an alumina composite oxide. The alumina composite oxide was crushed by a hammer mill to obtain an alumina composite oxide of Comparative Example 5.

[0461] (Comparative Example 6)

[0462] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 50 g in terms of zirconium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution. After the aqueous solution was kept at 180° C. for 2 hours in an autoclave, a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of a cerium oxide-zirconia composite oxide.

[0463] Next, the precipitate was recovered and washed by solid-liquid separation. The solid portion was fired in an electric furnace at 900° C. for 5 hours in the atmosphere to obtain a cerium oxide-zirconia composite oxide. The cerium oxide and zirconium oxide composite oxide were mixed with aluminum oxide (Sumitomo Chemical, AKP-G07, 42 g in terms of aluminum dioxide) and crushed with a hammer mill to obtain an aluminum oxide composite oxide of Comparative Example 6.

[0464] (Comparative Example 7)

[0465] Aluminum nitrate nonahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 42 g in terms of aluminum dioxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 50 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 3%, thereby preparing an aqueous nitrate solution.

[0466] Next, 400 g of ammonium bicarbonate was dissolved in 7600 g of ion exchange water to prepare a 5% ammonium bicarbonate aqueous solution. Next, the nitrate aqueous solution was added to the ammonium bicarbonate aqueous solution to obtain a precursor precipitate of an alumina-based composite oxide.

[0467] Next, the precipitate was recovered and washed by solid-liquid separation. The solid portion was fired in an electric furnace at 900° C. for 5 hours in the atmosphere to obtain an alumina composite oxide. The alumina composite oxide was crushed by a hammer mill to obtain an alumina composite oxide of Comparative Example 7.

[0468] (Comparative Example 8)

[0469] Cerium (IV) diammonium nitrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 50 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution. After the aqueous solution was kept at 180° C. for 2 hours in an autoclave, a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of a cerium oxide-zirconia composite oxide.

[0470] Next, the precipitate was recovered and washed by solid-liquid separation. The solid portion was fired in an electric furnace at 900° C. for 5 hours in the atmosphere to obtain a cerium oxide-zirconia composite oxide. The cerium oxide and zirconium oxide composite oxide were mixed with aluminum oxide (Sumitomo Chemical, AKP-G07, 42 g in terms of aluminum dioxide) and crushed with a hammer mill to obtain an aluminum oxide composite oxide of Comparative Example 8.

[0471] (Comparative Example 9)

[0472] Aluminum nitrate nonahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 30 g in terms of aluminum dioxide), zirconium oxynitrate (Mitsuwa Chemical Industry, special grade reagent, 44 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 3%, thereby preparing an aqueous nitrate solution.

[0473] Next, 400 g of ammonium bicarbonate was dissolved in 7600 g of ion exchange water to prepare a 5% ammonium bicarbonate aqueous solution. Next, the nitrate aqueous solution was added to the ammonium bicarbonate aqueous solution to obtain a precursor precipitate of an alumina-based composite oxide.

[0474] Next, the precipitate was recovered and washed by solid-liquid separation. The solid portion was fired in an electric furnace at 900° C. for 5 hours in the atmosphere to obtain an alumina composite oxide. The alumina composite oxide was crushed by a hammer mill to obtain an alumina composite oxide of Comparative Example 9.

[0475] (Comparative Example 10)

[0476] Zirconium oxychloride octahydrate (Mizuwa Chemical, special grade reagent, 44 g in terms of zirconium oxide) was dissolved in ion exchange water, and then adjusted to an acid concentration of 0.67 N and a ZrO2 concentration of 4 wt / vol% using 35% hydrochloric acid and ion exchange water. The temperature of the aqueous solution was adjusted to 120°C and the pressure was adjusted to 2×10 5 After Pa, 650 g of a 5% sodium sulfate aqueous solution was added and the mixture was kept for another 15 minutes. Then, the mixture was cooled to room temperature to obtain a slurry containing basic zirconium sulfate.

[0477] Next, cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of yttrium oxide) were added to the slurry containing basic zirconium sulfate, and a 25% sodium hydroxide aqueous solution was added until the pH reached 13, thereby obtaining a precipitate. The precipitate was then recovered and washed by solid-liquid separation.

[0478] The solid part was fired in an electric furnace at 900° C. for 5 hours in the atmosphere to obtain a cerium oxide-zirconia composite oxide. The cerium oxide and zirconia composite oxide were mixed with aluminum oxide (Sumitomo Chemical, AKP-G07, 30 g in terms of aluminum dioxide) and pulverized with a hammer mill to obtain an aluminum oxide composite oxide of Comparative Example 10.

[0479] (Comparative Example 11)

[0480] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 44 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide) and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide) were dissolved in ion exchange water, and a hydrogen peroxide solution in an amount 1.2 times the molar amount of cerium in cerium nitrate was added and stirred to obtain a raw material solution. The aqueous solution was stirred while adding ammonia water in an amount 1.2 times the amount of metal cations to neutralize, thereby obtaining a precursor precipitate of a cerium oxide-zirconia composite oxide. The precipitate was then fully washed by centrifugal separation, dried in air at a temperature of 150° C. for 7 hours, and pre-fired at 330° C. for 5 hours to obtain a molded body. The molded body was pulverized with a pulverizer and then fired in air at 800° C. for 5 hours to obtain a ceria-zirconia composite oxide.

[0481] Aluminum nitrate nonahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 30 g in terms of aluminum dioxide) was dissolved in ion exchange water. The cerium oxide and zirconium oxide composite oxide were suspended in the aluminum nitrate aqueous solution and stirred for 3 hours. The water was further evaporated by heating while stirring. The remaining solid matter was kept at 110°C for 40 hours in an atmospheric environment and then fired at 800°C for 5 hours to obtain the aluminum oxide composite oxide of Comparative Example 11.

[0482] (Comparative Example 12)

[0483] Aluminum nitrate nonahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of aluminum dioxide), zirconium oxynitrate (Mitsuwa Chemical Industry, special grade reagent, 60 g in terms of zirconium oxide), cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 10 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 3%, thereby preparing an aqueous nitrate solution.

[0484] Next, 400 g of ammonium bicarbonate was dissolved in 7600 g of ion exchange water to prepare a 5% ammonium bicarbonate aqueous solution. Next, the nitrate aqueous solution was added to the ammonium bicarbonate aqueous solution to obtain a precursor precipitate of an alumina-based composite oxide.

[0485] Next, the precipitate was recovered and washed by solid-liquid separation. The solid portion was fired in an electric furnace at 900° C. for 5 hours in the atmosphere to obtain an alumina composite oxide. The alumina composite oxide was crushed by a hammer mill to obtain an alumina composite oxide of Comparative Example 12.

[0486] (Comparative Example 13)

[0487] Aluminum nitrate nonahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 20 g in terms of aluminum dioxide), zirconium oxynitrate (Mitsuwa Chemical Industry, special grade reagent, 70 g in terms of zirconium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 3%, thereby preparing an aqueous nitrate solution.

[0488] Next, 400 g of ammonium bicarbonate was dissolved in 7600 g of ion exchange water to prepare a 5% ammonium bicarbonate aqueous solution. Next, the nitrate aqueous solution was added to the ammonium bicarbonate aqueous solution to obtain a precursor precipitate of an alumina-based composite oxide.

[0489] Next, the precipitate was recovered and washed by solid-liquid separation. The solid portion was fired in an electric furnace at 900° C. for 5 hours in the atmosphere to obtain an alumina composite oxide. The alumina composite oxide was crushed by a hammer mill to obtain an alumina composite oxide of Comparative Example 13.

[0490] (Comparative Example 14)

[0491] Zirconium oxynitrate (Mizuwa Chemical, special grade reagent, 70 g in terms of zirconium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of lanthanum oxide), neodymium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 2 g in terms of neodymium oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd., special grade reagent, 4 g in terms of yttrium oxide) were dissolved in ion exchange water until the oxide equivalent reached 5%, thereby preparing a nitrate aqueous solution. After the aqueous solution was kept at 180° C. for 2 hours in an autoclave, a sodium hydroxide aqueous solution having a concentration of 25% by mass was added until the pH reached 9, thereby obtaining a precursor precipitate of a cerium oxide-zirconia composite oxide.

[0492] Next, the precipitate was recovered and washed by solid-liquid separation. The solid portion was fired in an electric furnace at 900° C. for 5 hours in the atmosphere to obtain a cerium oxide-zirconia composite oxide. The cerium oxide and zirconium oxide composite oxide were mixed with aluminum oxide (Sumitomo Chemical, AKP-G07, 20 g in terms of aluminum dioxide) and crushed with a hammer mill to obtain an aluminum oxide composite oxide of Comparative Example 14.

[0493] (Comparative Example 15)

[0494] In a stirred tank, 34.7 kg of deionized water, 10.95 kg of aluminum sulfate solution having an aluminum oxide (Al2O3) concentration of 8.31 wt%, 1.43 kg of lanthanum nitrate solution having a La2O3 concentration of 26.9 wt%, and 4.97 kg of a 68 wt% nitric acid aqueous solution were added to prepare solution (A). Solution (B) was a sodium aluminate solution having an aluminum oxide (Al2O3) concentration of 24.9 wt%.

[0495] 71 kg of deionized water was added to a stirred reactor (250 rpm, four blades with a 45° inclined shaft). The reactor was then heated to a temperature of 65°C. This temperature was maintained throughout the reaction. 69% nitric acid solution was added to the stirred reactor until a pH of 3 was reached.

[0496] Solution (A) and solution (B) were simultaneously added to the stirred reactor through an inlet tube near the stirring shaft. Solution (A) was added at a flow rate of 1.05 kg / min. Solution (B) was added at a flow rate that allowed the pH to reach 5 within 3 minutes. The flow rate of solution (A) was kept constant at 1.05 kg / min, and the flow rate of solution (B) was adjusted to a value that maintained the pH at 5.1 within 46 minutes.

[0497] The introduction of solution (A) was stopped, and solution (B) was added continuously for 15 minutes until the pH reached 10. Then, the reaction slurry was injected into a vacuum filter. After the filtration, the filter cake was washed with deionized water at 60°C. Then, the filter cake was redispersed in deionized water to obtain a suspension of oxide (Al2O3-La2O3) with a concentration of 8% by weight. The suspension was spray-dried to obtain a dried lanthanum-doped aluminum hydrate powder (aluminum hydrate 1).

[0498] In a tank stirred by a shaft having four blades inclined at 45°, 357 g of water, 114 g of zirconium nitrate solution (21 g in terms of zirconium oxide), 56 g of CeIII nitrate solution (16.2 g in terms of cerium oxide), 4.4 g of lanthanum nitrate solution (1.2 g in terms of lanthanum oxide), and 16 g of yttrium nitrate solution (2.4 g in terms of yttrium oxide) were added to prepare a solution mainly composed of nitrates of the precursors. Next, in order to obtain a precursor solution, 2.3 g of 69 wt% nitric acid was added to the obtained solution. While stirring, 28 g of aluminum hydrate 1 was added, which contained aluminum oxide (18 g of Al2O3) equivalent to 64.5 wt% and La2O3 (1.17 g) equivalent to 4.2 wt%. The precursor mixture was stirred continuously until a mixture was obtained in the form of a uniform dispersion. Next, 5.3 g of a 9.8 mol / L aqueous hydrogen peroxide solution was added. Continue stirring the precursor mixture.

[0499] The precursor mixture was added to a reactor (575 rpm) containing 500 mL of 2 mol / L ammonia solution and stirred by a shaft with four blades inclined at 45°, at ambient temperature for 60 minutes. After the addition of the precursor mixture, the mixture was heated to a temperature of 95°C and maintained at this temperature for 30 minutes. The mixture was then cooled to a temperature of less than 40°C. 12 g of lauric acid was added to the cooled mixture while stirring at 650 rpm. The stirring was maintained for 30 minutes.

[0500] The mixture was filtered under vacuum, and then the filter cake was washed with 720 g of an aqueous ammonia solution of pH = 9. Then, the obtained wet cake was placed in a muffle furnace. The temperature of the furnace was raised to 950°C at a rate of 4°C / min, and then the temperature was maintained for 4 hours. After the firing was completed in air, a mixed oxide was obtained. The recovered mixed oxide was then crushed in a mortar. This was used as the alumina composite oxide of Comparative Example 15.

[0501] (Comparative Example 16)

[0502] In a stirred tank, 34.7 kg of deionized water, 10.95 kg of aluminum sulfate solution having an aluminum oxide (Al2O3) concentration of 8.31 wt%, 1.43 kg of lanthanum nitrate solution having a La2O3 concentration of 26.9 wt%, and 4.96 kg of a 68 wt% nitric acid aqueous solution were added to prepare solution (A). Solution (B) was a sodium aluminate solution having an aluminum oxide concentration of 24.9 wt%.

[0503] 71 kg of deionized water was added to a stirred reactor (250 rpm, four blades with a 45° inclined shaft). The reactor was then heated to a temperature of 65°C. This temperature was maintained throughout the reaction. 69% nitric acid solution was added to the stirred reactor until the pH reached 3.

[0504] Solution (A) and solution (B) were simultaneously introduced into the stirred reactor through an inlet pipe near the stirring shaft. Solution (A) was added at a flow rate of 1.05 kg / min. Solution (B) was added at a flow rate that allowed the pH to reach 4.4 within 3 minutes. The flow rate of solution (A) was kept constant at 1.05 kg / min, and the flow rate of solution (B) was adjusted to a value that allowed the pH to remain at 4.4 within 46 minutes.

[0505] Stop introducing solution (A) and continue adding solution (B) for 15 minutes until the pH reaches 10. Then, inject the reaction slurry into a vacuum filter. After filtration, wash the filter cake with deionized water at 60°C. Then, redisperse the filter cake in deionized water to obtain a suspension of oxide (Al2O3-La2O3) with a concentration of 8% by weight. The suspension is spray-dried to obtain a dried lanthanum-doped aluminum hydrate powder (aluminum hydrate 2).

[0506] In a tank stirred with a shaft having four blades inclined at 45°, 357 g of water, 114 g of zirconium nitrate solution (21 g in terms of zirconium oxide), 56 g of CeIII nitrate solution (16.2 g in terms of cerium oxide), 4.4 g of lanthanum nitrate solution (1.2 g in terms of lanthanum oxide), and 16 g of yttrium nitrate solution (2.4 g in terms of yttrium oxide) were added to prepare a solution mainly composed of nitrates of the precursor. Next, in order to obtain a precursor solution, 2.3 g of 69 wt% nitric acid was added to the obtained solution. While stirring, 31.1 g of aluminum hydrate 2 containing aluminum oxide (18 g of Al2O3) equivalent to 57.8 wt% and La2O3 (1.18 g) of 3.8 wt% was added. The precursor mixture was stirred until a mixture was obtained in the form of a uniform dispersion. Next, 5.3 g of 9.8 mol / L aqueous hydrogen peroxide solution was added. Continue stirring the precursor mixture.

[0507] In a stirred reactor (600 rpm, four blades with an axis inclined at 45°), 500 mL of a 2 mol / L ammonia solution was added. The precursor mixture was added to the stirred reactor over 60 minutes. This step was performed at ambient temperature. After the addition of the precursor mixture, the mixture was heated to a temperature of 95°C and maintained at this temperature for 30 minutes. The reaction medium was then cooled to a temperature of less than 40°C. 12 g of lauric acid were added to the cooled mixture while stirring at 500 rpm. The stirring was maintained for 30 minutes.

[0508] The reaction medium was filtered under vacuum, and then the filter cake was washed with 1L of ammonia solution (pH = 9). Then, the obtained wet cake was placed in a muffle furnace. The temperature of the furnace was raised to 950°C at a rate of 4°C / min, and then the temperature was maintained for 4 hours. After the firing was completed in the air, a mixed oxide was obtained. The recovered mixed oxide was then crushed in a mortar. This was used as the alumina composite oxide of Comparative Example 16.

[0509] [Composition determination]

[0510] The compositions (in terms of oxides) of the alumina-based composite oxides of Examples and Comparative Examples were analyzed using a wavelength dispersive X-ray fluorescence spectrometer ("ZSX PrimusII" manufactured by Rigaku).

[0511] [Point analysis using energy dispersive X-ray spectroscopy]

[0512] Energy dispersive X-ray spectroscopy was used to perform point analysis on the aluminum oxide composite oxides of the examples and comparative examples. Specifically, first, the samples were embedded in resin and the surfaces were polished. Then, a total of 50 point analyses were performed according to the following steps a to c.

[0513] <Steps>

[0514] a: From the particle images observed by a scanning electron microscope (JSM-6700F manufactured by JEOL), one particle image having a cross section of 4 μm or more in the longitudinal direction and 4 μm or more in the lateral direction is selected;

[0515] b: Composition analysis was performed at 25 measurement points at intervals of 1 μm within a range of 4 μm in the longitudinal direction and 4 μm in the lateral direction of the selected particle image;

[0516] c: Another particle image different from the particle image selected in step a is selected, and the same composition analysis as in step b is performed.

[0517] The 50 measured points were classified as follows, and the numbers of the respective points were summarized in a table. The results are shown in Tables 1 to 6.

[0518] It should be noted that in the comparative example, an example of a particle having a core-shell structure is shown. In this example, a region of 1 μm or more from the particle end to the particle center in the particle image is analyzed as a core portion (particle portion).

[0519] <Classification>

[0520] The number of points where the aluminum oxide content is less than 1 mass %;

[0521] The number of measurement points where the aluminum oxide content is 1 mass % or more and less than 50 mass % and the content of the oxide of an element other than aluminum oxide is 50 mass % or less and less than 99 mass %;

[0522] The number of measurement points at which the aluminum oxide content is 50 mass % or more and 99 mass % or less and the content of the oxide of the element other than aluminum oxide is 1 mass % or more and 50 mass % or less;

[0523] The number of points where the aluminum oxide content exceeds 99 mass %;

[0524] The number of measurement points at which the aluminum oxide content is 1 mass % or more and 45 mass % or less and the content of the element oxide other than aluminum oxide is 55 mass % or more and 99 mass % or less;

[0525] The number of measurement points at which the aluminum oxide content is 55 mass % or more and 99 mass % or less and the content of the oxide of the element other than aluminum oxide is 1 mass % or more and 45 mass % or less;

[0526] The number of measurement points at which the aluminum oxide content is 1 mass % or more and 40 mass % or less and the content of the element oxide other than aluminum oxide is 60 mass % or more and 99 mass % or less;

[0527] The number of measurement points at which the aluminum oxide content is 60 mass % or more and 99 mass % or less and the content of the oxide of the element other than aluminum oxide is 1 mass % or more and 40 mass % or less.

[0528] In addition, the maximum value, the minimum value, and the difference between the maximum value and the minimum value of the aluminum oxide content at the 50 measurement points are also shown in Tables 1 to 6.

[0529] Tables 1 to 6 also show the maximum and minimum values ​​of the contents of oxides of elements other than aluminum oxide at the 50 measurement points, as well as the difference between the maximum and minimum values.

[0530] [Measurement of pore volume]

[0531] For the aluminum oxide composite oxides of the examples and comparative examples, a pore distribution measuring device ("BELSOAPMini II" manufactured by MicrotracBEL Corp) was used to obtain nitrogen adsorption and desorption isotherms, and then the pore distribution was calculated from the desorption process using the BJH method. The measurement conditions are as follows. Then, the pore volume within the total range of the pore diameter distribution (pore diameter greater than or equal to 3nm and less than 200nm) was calculated. The results are shown in the table:

[0532] <Measurement conditions>

[0533] Measuring device: pore distribution measuring device (BELSOAP Mini II manufactured by MicrotracBEL Corp);

[0534] Measurement range: Pe / P0=0~1;

[0535] Adsorption temperature: 77K;

[0536] Number of measurement points: 10 points on the adsorption side and 25 points on the desorption side.

[0537] [Measurement of Rh particle size (catalyst particle size)]

[0538] In the alumina composite oxide of the embodiment and the comparative example, an 8% Rh nitrate solution (produced by Tanaka Precious Metals Industry) with 2% by weight of Rh was impregnated, dried at 100°C, and then calcined at 500°C for 5 hours to obtain a Rh-loaded powder. Next, a heat treatment was performed at 1200°C for 12 hours in an atmospheric environment to obtain a sample. 0.2 g of the sample was weighed in a sample cell, and the Rh particle size was measured by a CO pulse method using a BELCAT B manufactured by MicrotracBEL Corp. The results are shown in Tables 1 to 6.

[0539] As can be seen from Tables 1 to 6, when the alumina-based composite oxides of Examples are used, aggregation of Rh (catalyst metal element) can be suppressed.

[0540] For ease of understanding, Figures 1 to 4 2 and 3 show a model diagram of the tertiary particles of the alumina-based composite oxide of the example and the tertiary particles of the alumina-based composite oxide of the comparative example.

[0541] like Figure 1 As shown, the alumina-based composite oxides 1 of Examples 1 to 34 are in the form of tertiary particles, which are composed of two secondary particles with different element distributions, namely:

[0542] Secondary particles 2 having an aluminum oxide content of 50 mass % to 99 mass % (secondary particles 2 having an element oxide content other than aluminum oxide of 1 mass % to 50 mass %); and

[0543] The secondary particles 3 have an oxide content of an element other than aluminum oxide of greater than 50% by mass and less than 99% by mass (the secondary particles 3 have an aluminum oxide content of greater than 1% by mass and less than 50% by mass).

[0544] Therefore, even if exposed to a high temperature region for a long time, aggregation of the catalyst metal element can be suppressed.

[0545] like Figure 2 As shown, the alumina composite oxides 4 of Comparative Examples 1, 3-5, 7, 9, 12, and 13 are in the form of tertiary particles, but are composed only of secondary particles 5 with small element distribution deviations. That is, among the secondary particles, the difference between the maximum and minimum values ​​of the alumina content of the alumina composite oxides 4 of Comparative Examples 1, 3-5, 7, 9, 12, and 13 is small. Therefore, when exposed to a high temperature zone for a long time, the catalyst metal elements will condense.

[0546] like Figure 3 As shown, the aluminum oxide composite oxide 6 of Comparative Examples 2, 6, 8, 10, and 14 is in the form of tertiary particles, but is composed of secondary particles 7 and 8 whose element distributions have a significantly large deviation from each other. Among the secondary particles, the difference between the maximum and minimum values ​​of the aluminum oxide content of the aluminum oxide composite oxide 4 of Comparative Examples 2, 6, 8, 10, and 14 is significantly large. That is, the aluminum oxide composite oxide 6 of Comparative Examples 2, 6, 8, 10, and 14 is a tertiary particle that is a mixture of aluminum oxide particles and element oxides other than aluminum oxide, and the characteristics of element distribution caused by the composite between aluminum oxide and element oxides other than aluminum oxide are difficult to show. Therefore, when exposed to a high temperature zone for a long time, the catalyst metal element will condense.

[0547] like Figure 4As shown, the aluminum oxide composite oxide 9 of comparative example 11 is in the form of three-level particles, which are composed of secondary particles 10 constituting the shell and secondary particles 11 constituting the core. The secondary particles 10 and 11 are composed of secondary particles 7 and 8 having significantly large element distribution deviations. That is, the aluminum oxide composite oxide 9 of comparative example 11 is a three-level particle which is a mixture of aluminum oxide particles and element oxides other than aluminum oxide, and the characteristics of element distribution due to the composite between aluminum oxide and element oxides other than aluminum oxide are difficult to show. Therefore, when exposed to a high temperature zone for a long time, the catalyst metal element will condense.

[0548] [Particle size D 50 , particle size D 90 Determination of

[0549] 0.15 g of the alumina composite oxide of the example and the comparative example and 40 ml of 0.2% sodium hexametaphosphate aqueous solution were placed in a 50 ml beaker, dispersed in an ultrasonic homogenizer "Sonifier-S-450D" (Emerson Co., Ltd., Japan) for 2 minutes, and then placed in an apparatus (laser diffraction particle size distribution measuring apparatus ("LA-950" manufactured by Horiba, Ltd.)) for measurement. The results are shown in Table 1.

[0550] [X-ray diffraction spectrum]

[0551] Using an X-ray diffraction device ( Rigaku), and obtained the X-ray diffraction spectrum of the alumina composite oxide of Example 1. The measurement conditions are as follows. Figure 5 Shown in.

[0552] <Measurement Conditions>

[0553] Measurement apparatus: X-ray diffraction apparatus (Rigaku manufactured, Ultima IV);

[0554] Line source: CuKα line source;

[0555] Tube voltage: 50kV;

[0556] Tube current: 30mA;

[0557] Scanning speed: 2θ = 20 to 65°: 4° / min.

[0558] Table 1

[0559]

[0560] Table 2

[0561]

[0562] Table 3

[0563]

[0564] Table 4

[0565]

[0566] Table 5

[0567]

[0568] Table 6

[0569]

Claims

1. An alumina-based composite oxide, characterized in that: contain: Alumina; and Cerium oxide and / or zirconium oxide, In the point analysis of a total of 50 points performed according to the following steps a to c using energy dispersive X-ray spectroscopy, all of the following requirements (1) to (4) are satisfied: (1) Among the 50 points, at least one measurement point exists where the aluminum oxide content is 50 mass % to 99 mass % and the content of the oxide of the element other than aluminum oxide is 1 mass % to 50 mass %; (2) Among the 50 points, at least one measurement point exists where the aluminum oxide content is 1 mass % or more and less than 50 mass % and the content of the oxide of the element other than aluminum oxide is 50 mass % or less and less than 99 mass %; (3) The difference between the maximum and minimum values ​​of the aluminum oxide content at the 50 measurement points is 20 or more and 95 or less; (4) The difference between the maximum and minimum values ​​of the content of oxides of elements other than aluminum oxide at 50 measurement points is 20 or more and 95 or less, <Steps> a: From the particle images observed by scanning electron microscopy, select a particle image with a cross section of more than 4 μm in the longitudinal direction and more than 4 μm in the lateral direction; b: Composition analysis was performed at 25 measurement points at intervals of 1 μm within a range of 4 μm in the longitudinal direction and 4 μm in the lateral direction of the selected particle image; c: Select another particle image different from the particle image selected in step a, and perform the same composition analysis as in step b.

2. The alumina-based composite oxide according to claim 1, characterized in that: In the 50-point point analysis, all of the following requirements (5) to (6) are also met: (5) Among the 50 points, at least one measurement point exists where the aluminum oxide content is 55 mass % to 99 mass % and the content of the oxide of the element other than aluminum oxide is 1 mass % to 45 mass %; (6) Among the 50 points, there is at least one measurement point where the aluminum oxide content is 1 mass % to 45 mass % and the content of the element oxide other than aluminum oxide is 55 mass % to 99 mass %.

3. The alumina-based composite oxide according to claim 1, characterized in that: In the 50-point point analysis, all of the following requirements (7) to (8) are also met: (7) Among the 50 points, there are 10 or more measurement points where the aluminum oxide content is 50 mass % or more and 99 mass % or less and the content of the oxide of the element other than aluminum oxide is 1 mass % or more and 50 mass % or less; (8) Among the 50 points, there are 10 or more measurement points where the aluminum oxide content is 1 mass % or more and less than 50 mass % and the content of the oxide of the element other than aluminum oxide is more than 50 mass % and less than 99 mass %.

4. The alumina-based composite oxide according to claim 2, characterized in that: In the 50-point point analysis, all of the following requirements (9) to (10) are also met: (9) Among the 50 points, there are 5 or more measurement points where the aluminum oxide content is 55 mass % or more and 99 mass % or less and the content of the oxide of the element other than aluminum oxide is 1 mass % or more and 45 mass % or less; (10) Among the 50 points, there are 5 or more measurement points where the aluminum oxide content is 1 mass % to 45 mass % and the content of the element oxide other than aluminum oxide is 55 mass % to 99 mass %.

5. The alumina-based composite oxide according to any one of claims 1 to 4, characterized in that: In the composition analysis by X-ray fluorescence method, the content of aluminum oxide was 15 mass % or more and 80 mass % or less.

6. The alumina-based composite oxide according to any one of claims 1 to 4, characterized in that: In a composition analysis by an X-ray fluorescence method, the content of cerium oxide and / or zirconium oxide is 0.1 mass % or more and 85 mass % or less.

7. The alumina-based composite oxide according to any one of claims 1 to 4, characterized in that: As the oxide other than aluminum oxide, ceria, and zirconium oxide, at least one oxide of a rare earth element other than cerium and promethium is included.

8. A method for producing an alumina-based composite oxide according to any one of claims 1 to 4, characterized in that: include: Step 1: adding acid to sodium aluminate to obtain hydrated alumina suspension A; Step 2: preparing an aqueous solution B-1 containing an industrial salt of cerium and / or zirconium and / or a suspension B-2 containing an industrial salt of cerium and / or zirconium; Step 3: obtaining a precipitate of an aluminum composite precursor by mixing the suspension A with the aqueous solution B-1 and / or the suspension B-2; and Step 4: The precipitate is heat-treated to obtain an alumina-based composite oxide.

Citation Information

Patent Citations

  • Composite metal oxide porous body, catalyst using same, and method for producing each

    WO2011030875A1